This is learning experience design : what it is, how it works, and why it matters - Floor, Niels (Voices that matter., 2023)
Learning Experience Design (LXD) offers a powerful new approach to creating memorable learning experiences that deliver superior outcomes, bridging the gap between creative design disciplines and the world of learning. Now, one of the field's leading pioneers has written the definitive guide to LXD: what it is, how it works, what's better about it, and how you can make the most of it. Drawing on over a decade of experience defining, applying, and teaching LXD, Niels Floor covers LXD mindsets, methods, skills, tools: everything you need to succeed. Floor guides you step-by-step through every stage of the LXD process, from preliminary questions and ideas to focused design research, prototyping to final design. Floor also introduces the world's #1 LXD tool, his own Learning Experience Canvas, together with key tools such as personas, empathy maps, and experience maps. Whether you're a professional learning designer, course developer, or corporate training specialist you'll find this guide invaluable. And if you're a creative professional, it'll open new vistas of opportunity in fast-growing marketplace for learning solutions.